Assessment of temozolomide action encapsulated in chitosan and polymer nanostructures on glioblastoma cell lines - C. Abrudan; I. S. Florian; A. Baritchii; O. Soritau; S. Dreve; C. Tomuleasa; B. Petrushev (Romanian Neurosurgery, 2014)
Purpose: Glioblastoma multiforme (GBM) remains one of the most devastating diseases known to mankind and affects more than 17,000 patients in the United States alone every year. This malignancy infiltrates the brain early in its course and makes complete neurosurgical resection almost impossible. Recent years have brought significant advances in tumor biology. Many cancers, including gliomas, appear to be supported by cells with stem-like properties. Nanoparticles are excellent candidates to serve as delivery vectors of drugs or biologically active molecules because of their unique chemical and physical properties that result in specific transportation and deposition of such agents in specific organs and tissues. In the current study we have investigated the in vitro action of nanostructural systems (temozolomide encapsulated in chitosan and polymer nanostructures) on high-grade glioma-derived cancer stem cells (CSCs), with the intention of developing a new therapy to treat specific brain tumors with increased efficacy and minimal toxicity. In vitro cytotoxicity and apoptosis measurements indicated that the drug/vector combination facilitated the ability of the alkylating drug TMZ to alter the resistance of these cancer stem cells, suggesting a new chemotherapy strategy even for patients diagnosed with inoperable or recurrent malignant gliomas. Methods: At the National Institute for R & D of Isotopic and Molecular Technologies form Cluj Napoca were synthesized three types of nanostructures chitosan-TMZ, TMZ-chitosan-PEG (poly-ethylene glycol), TMZ-chitosan-PPG (polypropylene glycol). Three type of cell lines (Glioma-derived stem, HFL and HUVEC) were treated with the 3 types of nanostructures and the survival rate of the cells was compare to standard therapy (TMZ). Results: The results showed a reduction in the rate of survival of the tumor cells. Cell proliferation assays clearly demonstrate the differences between conventional chemotherapy (TMZ) and temozolomide encapsulated in chitosan and polymer nanostructures. Conclusion: Nanostructures like chitosan, PEG, PPG are useful as vectors for drugs transport. Despite combined therapy (surgery, radiotherapy, chemotherapy), currently median patient survival is reduced. The key to improving life expectancy could be an effective therapy targeted, customized for each case. An increasingly important role will be new methods of treatment such as immunotherapy, gene therapy or nanotherapy.